Pengaruh jumlah kendaraan bermotor, jumlah penduduk dan kebijakan pemerintah terhadap pertumbuhan ekonomi melalui penerimaan pajak kendaraan bermotor (PKB) di Provinsi Jambi - Hadi Tiawan; Erfit Erfit; Zulgani Zulgani (Konsentrasi Pembangunan Regional dan Publik, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2020)
This study aims to: (1) To find out and analyze the influence of the number of motorized vehicles, population, and government policy on the acceptance of PKB in Jambi Province in the period 2000-2018, and (2) To find out and analyze the influence of the number of motorized vehicles, population, government policies and PKB's acceptance of economic growth in Jambi Province in the period 2000-2018. This study uses the Path Analysis method. Based on the results of the study that the independent variable that affects motor vehicle tax revenue is the population. The results of the path analysis for structural equation I, namely the contribution of the population in Jambi Province directly have a positive impact on motor vehicle tax revenues in Jambi Province. Furthermore, the independent variables that influence economic growth are the number of vehicles and the population. The results of the path analysis for structural equation II namely the contribution of the number of motorized vehicles in Jambi Province directly have a positive impact and the indirect effect through the population contributes negatively to economic growth in Jambi Province. Furthermore, the contribution of the population in Jambi Province directly has a positive impact and the indirect effect through the number of motor vehicles contributes negatively to economic growth in Jambi Province. Keywords: Motorized vehicles, Population, Government policy, Motorized vehicle tax revenue, Economic growth.